The dimensions of spaces of holomorphic second-order cusp forms with characters - Blann, Thomas (2012)
To each pair of characters $(χ,ψ)$ on a Fuchsian group of the first kind we associate a space of functions generalizing the space of second--order cusp forms. We determine the dimensions of these spaces and construct explicit bases. We separate two cases according to the weight. The first case deals with weight higher than 2 whilst the second deals with the more complicated case of weight 2.